Analysis of Factors That May Affect the Effect of Atropine 0.01% on Myopia Control - Zhang, Xiaoyu; Wang, Yuliang; Zhou, Xingtao; Qu, Xiaomei (Frontiers in Pharmacology, 2020)
Children respond differently to atropine treatment, and predicting patient factors associated with better myopia control is important. Therefore, we aimed to evaluate factors related to myopia progression in Chinese children treated with atropine 0.01%. This retrospective study included 133 children who were administered atropine 0.01% eyedrops every night for 1 year. Enrolled children were examined at follow-up visits at 3 and 6 months and 1 year. The primary outcome was clinically significant myopia progression (over a -0.75 diopter (D) increase in spherical equivalent (SE)). Multivariate logistic analysis was used to identify predictive factors for myopia progression. The mean baseline SE was -3.92±2.76D, and the average increase in SE and axial length at 1 year from baseline were -0.55±0.57D and 0.43±0.52 mm, respectively. The risk of myopia progression significantly increased in children whose mothers had moderate myopia of less than -6D compared to that in children whose mothers had no history of myopia (odd ratio [OR] = 2.76, 95% confidence interval [CI]: 1.06 to 7.19, P = 0.0382). Birth by cesarean section was also a risk factor for myopia progression (odd ratio [OR] = 2.35, 95% CI: 1.30 to 4.27, P = 0.0048). Correlation between SE and treatment efficiency was linear, and the risk of myopia progression significantly decreased with increasing SE. Atropine 0.01% controlled myopia more effectively in children with higher myopia, who were delivered naturally, and whose mothers had no genetic background of myopia.